Decorating polyelectrolyte wrapped SWNTs with CdTe quantum dots for solar energy conversion - Leubner, Susanne; Katsukis, Georgios; Guldi, Dirk Michael (Faraday Discussions, 2012)
We report herein on the development of a synthetic route towards SWNT/polyelectrolyte/QD nanohybrids. On one hand, negatively charged thioglycolic acid capped CdTe QDs were prepared via an aqueous solution based synthesis. On the other hand, SWNTs were coated with a positively charged polyelectrolyte. By virtue of electrostatic interactions between QDs and SWNTs, SWNT/polyelectrolyte/QD nanohybrids were realized, whose formation was corroborated by thorough spectroscopic and microscopic investigations. Of particular relevance are changes of the QD related emission - quantum yields and lifetimes - upon their integration into the nanohybrids. The latter is indicative for electronic communication between both the photo- and redoxactive constituents, namely QDs and SWNTs, whose nature is electron transfer. © 2012 The Royal Society of Chemistry.